2020
DOI: 10.1002/smll.201906744
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Oxide Particles Catalytically Generate Nitric Oxide from Endogenous and Exogenous Prodrugs

Abstract: Nitric oxide (NO) is a potent biological molecule that contributes to a wide spectrum of physiological processes. However, the full potential of NO as therapeutic agents is significantly complicated by its short half-life and limited diffusion distance in human tissues. Current strategies for NO delivery focus on encapsulation of NO donors into prefabricated scaffolds or an enzyme-prodrug therapy approach. The former is limited by the finite pool of NO donors available, while the latter is challenged by the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 42 publications
(37 reference statements)
0
29
0
Order By: Relevance
“…There are various strategies to administer additional NO to the body; some of these are early stage technologies, while others have made it to the clinics. [ 26 ] NO can be introduced via catalytic generation using enzymes or enzymes mimics with NO donors endogenously present in the body, [ 26,81,82 ] as well as through the delivery of exogenous NO‐releasing species [ 83 ] (Figure 1). Exogenous NO donors have been synthesized and published in great numbers, and several have been translated to the clinic (although, with rare exceptions, not for the treatment of viral diseases).…”
Section: No‐based Therapies To Fight Viral Infectionsmentioning
confidence: 99%
“…There are various strategies to administer additional NO to the body; some of these are early stage technologies, while others have made it to the clinics. [ 26 ] NO can be introduced via catalytic generation using enzymes or enzymes mimics with NO donors endogenously present in the body, [ 26,81,82 ] as well as through the delivery of exogenous NO‐releasing species [ 83 ] (Figure 1). Exogenous NO donors have been synthesized and published in great numbers, and several have been translated to the clinic (although, with rare exceptions, not for the treatment of viral diseases).…”
Section: No‐based Therapies To Fight Viral Infectionsmentioning
confidence: 99%
“…In such a case, endogenous substrates can be envisioned to provide basal level NO, whereas exogenous NO prodrugs can be used as supplements, to enhance NO levels when needed. The first few reports that present such opportunities (using metallic particles) appear to be promising, [78,86,90] and this avenue of research appears to be rewarding. Understanding the catalytic mechanisms of enzyme mimics for NO release, for example using density functional theory calculations, [119,120] will provide insights into substrate selectivity.…”
Section: Discussionmentioning
confidence: 99%
“…[87][88][89] In our recent work, we discovered that ZnO particles mimicked the activities of β-galactosidase and glutathione peroxidase, and catalyzed both exogenous (β-gal-NONOate) and endogenous (GSNO) NO donors to generate NO. [90] We achieved physiologically relevant NO levels, ranging from 0.1 µM to 2.2 µM, by simply modulating the concentrations of GSNO and ZnO. After 6-month incubation in PBS, ZnO particles preserved their catalytic potency, which is highly beneficial towards long-term biomedical applications.…”
Section: Other Metalsmentioning
confidence: 99%
“…The NO release profiles showed that the release rate sustained up to 5 days with good thrombo-resistant effect. As thrombus involves the formation of fibrin and activation of platelets, Yang et al proposed a novel concept to integrate anti-coagulant agent bivalirudin (BVLD) and NO as a bulk synergetic modification on surface coating (Yang et al, 2020b ). BVLD was covalently connected with the primary amine groups on plasma polymerized allylamine (PPAm)-coated surface, and then the coating was immersed in basic solution under high-pressure NO gas to form a NONOate-like bulk depot.…”
Section: No-releasing Coatingsmentioning
confidence: 99%